2017
DOI: 10.1111/idj.12260
|View full text |Cite
|
Sign up to set email alerts
|

A global probe into dental student perceptions about philanthropy, global dentistry and international student exchanges

Abstract: The study suggests that dental students would value international exchanges, which may enhance students' knowledge and self-awareness related to cultural competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Burgess et al found an increase in cultural competence among students who were exposed to a diversity of patients in clinical training 26 . Furthermore, international exchange missions have been found to be an important component to improving cultural competence among dental students across the world 27 . Interactions with people who are different from oneself reduce an individual's implicit biases of others and increases cultural competence.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess et al found an increase in cultural competence among students who were exposed to a diversity of patients in clinical training 26 . Furthermore, international exchange missions have been found to be an important component to improving cultural competence among dental students across the world 27 . Interactions with people who are different from oneself reduce an individual's implicit biases of others and increases cultural competence.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 As standards and principles of sustainable global health experiences evolve, dental schools may consider offering and encouraging students to engage in longer experiences. 31,32 As standards and principles of sustainable global health experiences evolve, dental schools may consider offering and encouraging students to engage in longer experiences.…”
Section: Role Of Dental Educationmentioning
confidence: 99%
“…Predoctoral programs should also provide didactic foundational learning in the principles of global health to help students think critically about volunteer programs and identify more sustainable opportunities if pursued outside the school through religious organization or NGOs. 31,32 As standards and principles of sustainable global health experiences evolve, dental schools may consider offering and encouraging students to engage in longer experiences. Such programs may present a challenge from a financial perspective and with respect to time spent away from school; however, partnering with local community organizations and universities in host countries may help alleviate these constraints.…”
Section: Role Of Dental Educationmentioning
confidence: 99%
“…Contemporary global educational trend of encouraging student and staff exchange is especially emphasized in Europe through programmes supporting the free movement of students across EU ( 22 ). Students from different countries found that international exchanges could enhance students’ knowledge and self‐awareness related to cultural competence ( 23 ). This global trend brings students from different cultural backgrounds in interaction highlighting the importance of appreciating students’ needs and their perception of learning environment in order to facilitate their accommodation in a host country.…”
Section: Discussionmentioning
confidence: 99%